Processing of activated carbon from Malaysian Carbonaceous resources ... [et al.] / [microfilm] - Muhd Abdullah Shukran Sa'dan (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2001